AN ANALYSIS OF INDONESIAN-ENGLISH CODE MIXING PRODUCED BY BOY WILLIAM IN A YOUTUBE VLOG - Alawiyyah, Anisa; Nuari Ramadhan, Zetta (Dialectical Literature and Educational Journal, 2024)
This study explores the occurrence of code mixing in communication. It aims to analyze the types of Indonesian-English code-mixing used by Boy William in his vlog, based on Muysken's theory, and to identify the reasons behind this code-mixing according to Hoffman's theory. Conducted as a qualitative study, the data is presented in an analytic-descriptive manner. The data was sourced from Boy William's YouTube vlog titled “Maudy Ayunda Sempat Merasa Insecure Berada di Stanford”. After collecting the data, the researchers categorized and analyzed the types of code-mixing according to Muysken's (2000) theory and the reasons for code-mixing as per Hoffman's (1991) theory. The findings revealed 34 instances of code mixing in Boy William's speech, categorized into three types: 11 instances (32%) of insertion, 18 instances (53%) of alternation, and 5 instances (15%) of congruent lexicalization. The study also identified the reasons behind the code-mixing: 9 instances (26%) were for discussing specific topics, 2 instances (6%) involved quoting someone else, 4 instances (12%) were to show empathy, 4 instances (12%) were interjections, 3 instances (9%) involved repetition for clarification, 7 instances (20%) were for clarifying speech for the listener, and 5 instances (15%) were to express group identity.